2020
DOI: 10.1158/1541-7786.mcr-20-0289
|View full text |Cite
|
Sign up to set email alerts
|

The Bromodomain Inhibitor PFI-3 Sensitizes Cancer Cells to DNA Damage by Targeting SWI/SNF

Abstract: Many chemotherapeutic drugs produce double-strand breaks (DSB) on cancer cell DNA, thereby inducing cell death. However, the DNA damage response (DDR) enables cancer cells to overcome DNA damage and escape cell death, often leading to therapeutic resistance and unsuccessful outcomes. It is therefore important to develop inhibitors that target DDR proteins to render cancer cells hypersensitive to DNA damage. Here, we investigated the applicability of PFI-3, a recently developed bromodomain inhibitor specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…BRG1 promotes DNA strand breaks through nucleosome repositioning and altered recruitment of repair factors 39,40 . The BRG‐1/BRM inhibitor PFI‐3 exerts its DNA‐sensitising effects of doxorubicin in cancer cells by inhibiting DNA repair 41 . In contrast, the results described herein suggest that TEDs increase the amount of DNA breaks induced by TMZ and bleomycin.…”
Section: Discussionmentioning
confidence: 59%
“…BRG1 promotes DNA strand breaks through nucleosome repositioning and altered recruitment of repair factors 39,40 . The BRG‐1/BRM inhibitor PFI‐3 exerts its DNA‐sensitising effects of doxorubicin in cancer cells by inhibiting DNA repair 41 . In contrast, the results described herein suggest that TEDs increase the amount of DNA breaks induced by TMZ and bleomycin.…”
Section: Discussionmentioning
confidence: 59%
“…In general, and after reviewing various evidence that showed a contrast in the use of EZH2 inhibitors in cancers, especially mesothelioma, it seems that testing the response to EZH2 should be carefully evaluated before using these molecules as therapy ( 64 ). Recent research has shown that a novel bromodomain inhibitor called PFI-3, which targets SWI/SNF, and is responsible for repairing double-strand breaks in cancer, synergistically sensitizes many human cancers cell lines against DNA damage caused by chemotherapeutic agents such as doxorubicin ( 65 ). PFI-3 is a selective, potent, and cell-permeable SMARCA2/4 bromodomain inhibitor that has been previously characterized in the setting of various cancers (e.g., lung cancer, synovial sarcoma, leukemia, and rhabdoid tumors) ( 66 ).…”
Section: Swi/snf Component In Melanomamentioning
confidence: 99%
“…This study indicates mutations of SWI/SNF complex trigger carcinogenesis via inducing genome instability. Based on this hypothesis, a recently developed bromodomain inhibitor was proposed, targeting SWI/SNF complex to promote double-strand break and DNA repair [ 250 ], which demonstrates the feasibility for targeting SWI/SNF in cancer chemotherapy. Hong et al [ 251 ] reported carcinogenetic mechanisms of SMARCB1 and liver cancer.…”
Section: Key Structural Elements Mediating 3d Chromatin Interactionsmentioning
confidence: 99%